Advancing the 3Rs in regulatory ecotoxicology: A pragmatic cross‐sector approach. (1st November 2015) - Burden, Natalie; Benstead, Rachel; Clook, Mark; Doyle, Ian; Edwards, Peter; Maynard, Samuel K; Ryder, Kathryn; Sheahan, Dave; Whale, Graham; van Egmond, Roger; Wheeler, James R; Hutchinson, Thomas H
ABSTRACT: The ecotoxicity testing of chemicals for prospective environmental safety assessment is an area in which a high number of vertebrates are used across a variety of industry sectors. Refining, reducing, and replacing the use of animals such as fish, birds, and amphibians for this purpose addresses the ethical concerns and the increasing legislative requirements to consider alternative test methods. Members of the UK‐based National Centre for the Replacement, Refinement and Reduction of Animals in Research (NC3Rs) Ecotoxicology Working Group, consisting of representatives from academia, government organizations, and industry, have worked together over the past 6 y to provide evidence bases to support and advance the application of the 3Rs in regulatory ecotoxicity testing. The group recently held a workshop to identify the areas of testing, demands, and drivers that will have an impact on the future of animal use in regulatory ecotoxicology. As a result of these discussions, we have developed a pragmatic approach to prioritize and realistically address key opportunity areas, to enable progress toward the vision of a reduced reliance on the use of animals in this area of testing. This paper summarizes the findings of this exercise and proposes a pragmatic strategy toward our key long‐term goals—the incorporation of reliable alternatives to whole‐organism testing into regulations and guidance, and a culture shift toward reduced reliance on vertebrate toxicity testing in routine environmental safety assessment. Integr Environ Assess Manag 2016;12:417–421. © 2015 SETAC Key findings: There is much scope to advance the application of the 3Rs (replacement, refinement, and reduction in the use of animals) in regulatory ecotoxicity testing. A working group of experts in this field across academia, government organizations, and industry have identified the key drivers in which there are high demands on vertebrate testing, and have explored opportunities to address them. The group proposes a pragmatic strategy whereby key short‐, medium‐, and long‐term goals could be achieved to enable realistic progress in advancing the application of the 3Rs in this area. This evaluation will help to inform the development of high‐impact projects that facilitate the uptake of novel 3Rs approaches relevant to regulatory ecotoxicology.